The styles of illumination in Al-Qur'ans of the Malay world / N.H.M. Din, D.H.M. Zain and M. Mokhtar - Din, N.H.M.; Zain, D.H.M.; Mokhtar, M. (2016)
This paper about the styles of illuminationin AI-Qur'ans from the Malay world. The benchmark of each style is deriving from formidable regional identity with a distinctive style such as Aceh, Java, Terengganu and Middle East. Various criteria employ in analyze the illumination decoration in manuscript and to investigate the influences of illuminated AI-Qur'an from other part of the world to the Al-Qur'an of the Malay world. •The research concentrated on existing collection of illuminated Qur'an in museums and galleries. Anticipation from this research will establish the styles of illumination in AI-Qur'ans of the Malay world and perceive their own distinctive style, towards greater insight of the art in the Malay Manuscripts.